2009
DOI: 10.1002/jtr.743
|View full text |Cite
|
Sign up to set email alerts
|

International tourism and economic development in South Africa: a Granger causality test

Abstract: One of the major objectives of macroeconomic policies in many developing countries is sustained economic growth, and South Africa has been striving to achieve and maintain this in various ways. One of these is through international tourism. Although international tourism contributes to the growth of many economies, it is in turn, impacted by growth in many developed countries. Real gross domestic product (GDP), international tourism earnings, real effective exchange rate and exports were analysed within a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(96 citation statements)
references
References 30 publications
3
79
0
7
Order By: Relevance
“…Sarmidi and Saleh (2010) cross-country analysis (2009) showed a casual links between tourism and trade (export and import). Akinboade and Braimoh (2010) illustrated a causality links between real export and international tourism in long term.…”
Section: Resultsmentioning
confidence: 99%
“…Sarmidi and Saleh (2010) cross-country analysis (2009) showed a casual links between tourism and trade (export and import). Akinboade and Braimoh (2010) illustrated a causality links between real export and international tourism in long term.…”
Section: Resultsmentioning
confidence: 99%
“…However, despite using research methodologies based on time series and/or panel data analytical techniques, empirical studies have shown mixed or even inconsistent results in terms of supporting the tourism-led economic growth hypothesis. Examples of studies that analyze the relationship between tourism and economic growth employing the Granger causality test with time series data analysis include Balaguer and Cantavella-Jorda [9], Durbarry [10], Gunduz and Hatemi-J [11], Brida, Carrera, and Risso [12], Chen and Chiou-Wei [13], Belloumi [16], Akinboade and Braimoh [17], Tang and Abosedra [18], and Tang and Tan [19]. These studies provide evidence in support of the tourism-led growth hypothesis.…”
mentioning
confidence: 99%
“…In a key study showing the positive economic impact of tourism in Sub-Saharan Africa, Akinboade and Braimoh (2010) found that both in the short-and long-run, tourism receipts affect economic growth in South Africa; not the other way round. Arora and Vamvakidis (2010) also presented evidence of a direct correlation between tourism and GDP in South Africa, with the tourism variable Granger-causing real GDP.…”
Section: Literaturementioning
confidence: 99%